CRITICAL STUDY ON POLICY IMPLEMENTATION OF WITHDRAWAL OF PROVINCIAL ROAD RETRIBUTIONS BY THE GOVERNMENT OF TAMANSARI VILLAGE BASED ON GOVERNMENT REGULATION 97/2012: KAJIAN KRITIS PADA IMPLEMENTASI KEBIJAKAN PENARIKAN RETRIBUSI JALAN PROVINSI OLEH PEMERINTAH DESA TAMANSARI BERDASARKAN PERATURAN PEMERINTAH 97/2012 - Royatul Firdaus; Hary Priyanto; Erna Agustina (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Background: The road to Ijen Geopark is a provincial road that connects Banyuwangi Regency and Bondowoso Regency. The activity of collecting fees by the Tamansari Village Government for road users to Ijen Geopark which is intended to increase development in Tamansari Village has become a polemic in itself. The road to Ijen Geopark has 1 lane which has 2 lanes. Government Regulation 97/2012 explains that the road levy is for roads that have 2 lanes, each lane having at least 2 lanes. Objectives: To describe, analyze, and interpret the implementation of Tamansari Village Government policies in withdrawing provincial road fees for road users to Ijen Geopark based on Government Regulation 97/2012. Method: Using qualitative principles according to constructive and participatory models. Primary data from interviews, and secondary data from the results of literature studies and various regulations relevant to the substance of the research. Result: The fee collection program can be justified if it does not violate existing regulations and is properly beneficial for development and society. Conclusion: The wrong levy collection policy causes community dissatisfaction, causes people to have no sympathy for the government, and reduces the utilization of infrastructure provided by the government.